Nano-Composites Based on Ligno-Sulfonate and Titanium Oxide to Study Methylene Blue Removal and Photo-Degradation - Roa-Ruiz, K; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2024)
The dyes in minimum concentrations are toxic, cause visual and photosynthetic contamination in natural waters. For this reason, in this study, methylene blue (MB) adsorbent nano-composites were prepared based on variable percentages of sodium ligno-sulfonate (LS) (0.00–30.0 wt%) and titanium oxide nanoparticles (Np TiO2) (0.00–10.0 wt%) in sodium poly (4-styrene sulfonate) (P(SSNa)). Chemical, morphological, and thermal techniques corroborated the presence of the main functional groups of the nano-composites, with surfaces formed by macro-pores, and that of Np TiO2 showed an increase in the thermal stability of the material. On the other hand, from studies of hydration of the nano-composites, percentages higher than 4000 % were obtained with low dependence on pH effects, which could benefit the diffusion of the pollutant to the adsorbent in its adsorption. In relation to this, the MB retention capacity was evaluated by experimental parameters, such as % LS, % Np TiO2, pH, presence of ionic strength, contact time, MB concentration and amount of nano-composites. A maximum MB adsorption efficiency of 94.8 % and a capacity of 2886 mg g−1 were obtained using the P(SSNa)-based system with 20 % LS and 10 % Np TiO2. The obtained results were fitted to the pseudo-second order kinetic model and Langmuir and Redlich-Peterson isotherm models. In addition, through the synergistic effect of adsorption and photo-degradation, 97.5 % of the MB was removed within 1 h of irradiation. © 2024 Elsevier B.V.